Pengaruh Iklan “Shopee Versi COD” Terhadap Minat Beli Melalui Aplikasi Shopee Dikalangan Mahasiswa Program Studi D3 Administrasi Bisnis Politeknik Negeri Samarinda - Johan Lucas Away; ST. Nurhasanah; Ella Hariani (Politeknik Negeri Samarinda, 2022)
The marketing strategy that is currently being used is promotion through advertising. Advertising itself is a communication process that has an important power as a marketing tool in selling goods, providing services, and ideas through certain channels in the form of persuasive information. This study aims to analyze the influence of Shopee Advertisements